Modeling of the Trajectory of the Level Fluctuations in Lake Naroch - Kirvel, Ivan; Volchak, Alexander; Parfomuk, Sergey (Quaestiones Geographicae, 2016)
As a result of the conducted investigations of the level fluctuations in lake naroch the initial data are divided into 3 components: a polynomial regression that makes it possible to find out an independent on time law of trajectory, a periodic component of sinusoidal type and a residual sequence of independent random quantities. Modeling of the trajectory fluctuations is based on the deterministic part, consisting of the regression of the 8th order and periodic component, and also the random part, consisting of independent equally distributed quantities. Using this model it can be modeled the trajectory of the level fluctuations in lake naroch. The modeled trajectory by 200 years long demonstrated the probability of exceeding of maximum annual level, equal 1 per cent.